Biomedical Informatics for Sustainable Health Systems. Editorial - Geissbuhler, A.; Haux, R.; Kulikowski, C. (Yearbook of Medical Informatics, 2007)
To provide an editorial introduction to the 2007 IMIA Yearbook of Medical Informatics with an overview of its contents and contributors.A brief overview of the main theme of “Biomedical Informatics for Sustainable Health Systems”, and an outline of the purposes, contents, format, and acknowledgment of contributions for the 2007 IMIA Yearbook.In resonance with the MEDINFO 2007 conference theme “Building Sustainable Health Systems”, this issue of the Yearbook examines the role of healthcare informatics in helping face the challenge of sustainability for our health systems, through a number of original contributions, and selected papers published during the past 12 months.This timely topic, along with the review and surveys on the main streams of research in medical informatics, offer a complete overview of the development of our field. This current state of affairs is put in the perspective of the fortieth birthday of IMIA, reflecting on the past achievements of the Association, and outlining its potential to continue shaping the world of medical informatics.
Keywords: Editorial; 2007 IMIA Yearbook of Medical Informatics; sustainability of health systems; surveys of biomedical informatics; reviews of biomedical informatics; history of biomedical informatics; IMIA and its societies